The Impact of Time to Initiate Therapeutic Hypothermia on Short-Term Neurological Outcomes in Neonates with Hypoxic-Ischemic Encephalopathy - Till Dresbach; Viktoria Rigoni; Anne Groteklaes; Thomas Hoehn; Anja Stein; Ursula Felderhoff-Mueser; Andreas Mueller; Hemmen Sabir (MDPI AG, 2024)
Background: Therapeutic hypothermia is the standard treatment for neonates with hypoxic-ischemic encephalopathy. Preclinical evidence indicates that the time to initiate therapeutic hypothermia correlates with its therapeutic success. This study aims to explore whether there is a correlation between the early initiation of therapeutic hypothermia and improved short-term neurological outcomes in cooled asphyxiated newborns. Methods: A retrospective analysis was conducted, involving 68 neonates from two different neonatal intensive care units. The impact of time to initiate treatment, time to reach the target temperature, and time between initiation and target temperature was correlated with short-term outcomes on MRI. Results: We did not find a significant difference between outcomes regarding the time to start treatment and the time to achieve the target temperature. Interestingly, neonates with a poor outcome were treated on average earlier than neonates with a favorable outcome but required more time to reach the target temperature. Additionally, the study results did not support the hypothesis that a shorter time to initiate treatment would lead to shorter times to achieve the target temperature. Conclusion: Based on our findings, it is recommended to prioritize a thorough evaluation of neonatal encephalopathy before initiating therapeutic hypothermia. Early initiation of treatment should be balanced with the time required for precise assessment to ensure better outcomes.